Utilization Virtual Laboratory in Physics Learning: Bibliometric Analysis - Dwikoranto; Widiasih (Studies in Learning and Teaching, 2023)
This research aims to find out the trend of the author's topics and keywords that are widely used related to Virtual Lab Physics to find out future research opportunities. The research method used is descriptive analysis method research through the bibliometric approach. The results of a Google Scholar database search found 463,000 articles for 2016-2021 with the keywords "Virtual Lab Physics". Meanwhile, based on the Scopus database, Scopus-indexed articles were obtained for 2003-2021. Search results are stored in the form of RIS and CSV will then be analyzed using the VOSviewer application and Ms. Excel to obtain a visualization in the form of a bibliometric map. The results of data analysis show that the keywords often used and related to the Virtual Physics Lab during 2016-2021 are Physics, Engineering, Science, Physics Education Research, and Interest Laboratories. Indonesian researchers in contributing internationally are still lacking, this research topic is dominated in China and the United States of America with the document types being mostly conference papers. So far, research related to the topic of Virtual Lab Physics is still quiet so it has the potential to be developed. In addition, there are recommendations for Virtual Lab Physics research that can be collaborated with one of the related keywords, namely Engineering as an opportunity for research topics to be developed.